2019
DOI: 10.1021/acs.molpharmaceut.9b00416
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nab-Paclitaxel Delivery Using Microbubble-Assisted Ultrasound in a Pancreatic Cancer Model

Abstract: The combination of microbubbles and ultrasound is an emerging method for non-invasive and targeted enhancement of anticancer drugs uptake. This method showed to increase local drug extravasation in tumor tissue while reducing the systemic adverse effects in various tumor models. The present study aims into evaluating the therapeutic efficacy of this approach both in-vitro and in-vivo for Nab-paclitaxel delivery in a pancreatic tumor model. Ultrasound and microbubbles of different types in combination with Nab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
(131 reference statements)
0
24
0
Order By: Relevance
“…The study showed that the ultrasound microbubbles treatment group presented significant tumor growth inhibition (67). In addition, the use of nab-paclitaxel combined with ultrasound microbubbles significantly inhibited the activity of PDAC tumor cells in vitro and reduced the tumor volume in a subcutaneous PDAC mouse model (68). Furthermore, a clinical trial evaluated the efficacy of focused ultrasound combined with microbubble delivery of gemcitabine in PDAC patients.…”
Section: Remodeling Tumor Vasculaturementioning
confidence: 99%
“…The study showed that the ultrasound microbubbles treatment group presented significant tumor growth inhibition (67). In addition, the use of nab-paclitaxel combined with ultrasound microbubbles significantly inhibited the activity of PDAC tumor cells in vitro and reduced the tumor volume in a subcutaneous PDAC mouse model (68). Furthermore, a clinical trial evaluated the efficacy of focused ultrasound combined with microbubble delivery of gemcitabine in PDAC patients.…”
Section: Remodeling Tumor Vasculaturementioning
confidence: 99%
“…PTX toxicity arises not only from the drug itself but also from the high concentration of the Cremophor EL vehicle, which is required to solubilize the poorly aqueous PTX into an injectable solution. The most common toxicities associated with Cremophor EL include acute hypersensitivity reactions, which are recognizable as flushing, rash, dyspnea and tachycardia (Bhatt et al, 2019; Bressand et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…combined MBs‐assisted US with Nab‐paclitaxel to enhance intracellular uptake and significantly improve the therapeutic effectiveness of Nab‐paclitaxel in PDAC models. [ 259 ]…”
Section: Pdac‐tailored Nanomaterials For Therapeutic Strategiesmentioning
confidence: 99%